Management of Ocular Surface Squamous Neoplasia with Topical and Intralesional Interferon Alpha 2B in Mexicans - Nava-Castañeda, Ángel; Hernández-Orgaz, Joaquín; Garnica-Hayashi, Lilia; Ansart, Alberto; Matus, Gonzalo; Tovilla-Canales, José Luis; Zuazo, Francisca (Nepalese Journal of Ophthalmology, 2018)
Introduction: Ocular surface squamous neoplasia (OSSN) is the most common nonpigmented ocular surface neoplasm and it can originate from the conjunctiva and/ or corneal epithelium. Since the rate of recurrence after surgical excision is high, chemotherapeutic and immunotherapeutic agents such as interferon alpha-2b (IFN α-2b) have been used for its treatment. Objective: Our objective is to describe the demographic variables of patients with OSSN treated with IFN α-2b and to describe the outcomes of its use in Mexican patients, treated between 2011 and 2017 at Instituto de Oftalmología Fundación Conde de Valenciana. Materials and Methods: This is a non-randomized retrospective interventional case series. We reviewed the files of patients older than 18 years, with clinical and/or histopathological diagnosis of OSSN, treated with IFN α-2b alone or in combination with surgery, with a minimum of 6 months follow-up. We studied demographic variables, such as gender, age, eye affected and associated risks factors; we also studied the type of therapy with interferon (topical, intralesional and/or associated with surgery), time of treatment, time of follow up, recurrences and complications. Results: A total of 39 patients were included. The mean age of diagnosis was 61 ± 16 years and OSSN was more frequent in males (64.1% of cases). Most of the cases (43.6%) had no identifiable risk factors. The mean time of IFN α-2b treatment was 5 ± 2 months, being higher in the intralesional group (6.5 months) than in the topical group (4.2 months). The clinical resolution with the use of IFN α-2b was evidenced between 0.5 and 10 months, being achieved in 87.1% of the patients. Conclusions: The use of IFN α-2b is effective for the treatment of OSSN with a high success rate (87.1%) and a low incidence of relapse (5 cases), with no reported complications during follow up.